Investigating the horizontal carbon ecological compensation mechanism in the Yellow River Basin: construction, validation, and policy impact - Lu, Haiyan; Zhao, Xiaofei (Frontiers in Environmental Science, 2025)
Introduction: In order to improve ecological and environmental governance capacities, this study explores the creation and efficacy of a horizontal carbon ecological compensation, aiming to enhance ecological and environmental governance capabilities. The research addresses the critical need for innovative solutions to balance carbon emissions and ecological preservation in river basins, with the YRB serving as a primary case study.Methods: Net carbon emissions were computed for each YRB province using data from 2013 to 2022, 13 differentiating between carbon surplus and deficit locations. An evolutionary game model that examined dynamic interactions under incentive and punishment mechanisms was built using these computations as the foundation. Important elements affecting the ecological compensatory process for horizontal carbon were found. The viability of the system was demonstrated by the use of machine learning techniques to forecast net carbon 17 emissions under a voluntary trade scenario.Results: The findings show that the YRB’s carbon emission management and conservation may be greatly enhanced by market-based incentives and appropriate advice. The evolutionary game model revealed that integrating incentive and penalty mechanisms effectively promotes cooperation among provinces, leading to enhanced carbon management. Machine learning predictions further validated the potential of voluntary carbon trading to reduce net emissions, highlighting the practicality of the proposed compensation mechanism.Discussion: The results offer a theoretical framework for the YRB’s implementation of horizontal carbon ecological compensation. The proposed mechanism, founded on the trade of carbon emissions and backed by confirmation from machine learning, offers a novel approach to ecological protection. This model not only addresses the unique challenges of the YRB but moreover acts as a model for ecological management in other river basins., contributing to broader efforts in sustainable environmental management.